PEMBERONTAKAN WANITA DALAM NOVEL PRINCESS KARYA JEAN P. SASSON - Surjowati, Ribut (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
This paper reports a study of a struggle against gender inequalities as depicted in J.P Sasson’s Princess, a novel which reveals feminism spirit. The study examines the rebellion of an Arabic princess whose name is Sultana, who has a courage to fight against unfairness done by his father and most men in her country towards women. This study focuses on analysing the reasons of Sultana’s rebellions and her demands toward men in her family. The findings show that the reasons of Sultana’s rebellions are violence toward her female family members, woman marginalization and woman subordination. The demands for equality include equality between man and woman in rights and education.